Brave New Digital Classroom : Technology and Foreign Language Learning, Third Edition - Blake, Robert J., 1951-; Guillen, Gabriel A. (Book collections on Project MUSE., 2020)
Robert Blake, now with Gabriel Guillen, updates his successful book (1st ed. 2008, 2nd ed. 2013) on how to teach foreign languages using technology. Brave New Digital Classroom touches on all of the key concepts and challenges of teaching with technology of all kinds, focusing on issues specific to FLL or L2 learning. Originally referred to as computer-assisted language learning, CALL has come to encompass any kind of learning that uses digital tools for language learning. This book siginificantly updates and expands on the second edition reframing the conversation to account for the more integrated way technology is used in our lives. Starting at the beginning, Blake and Guillen ask, can technology help with L2? They then address the ways it can help, how to choose the right digital tools, how to use those tools effectively, finally expanding into a new area to explain how technology can impact literacy and identity. The book is primed for use in graduate courses. Key terminology is bolded and a comprehensive glossary is included. Each chapter finishes with a short list of references to consult for further reading on the topic and discussion questions. The authors will provide short interview videos (free via GUP website) to enhance discussions on the topics.